Positive psychology an international perspective - Chadee, Derek; Kostić, Aleksandra (John Wiley & Sons, Inc., 2021)
"Contributions by leading international authors who have critically engaged with the area. Among the well- known names contributing to this volume are: Paul Ekman, Robert Sternberg, Vittorio Caprara ;C. Daniel Batson; Illona Boniwell; Eve Ekman among others. Focus would be international but would particularly draw on authors from the UK, US, Serbia France, Italy, Caribbean, among others. The book would encourage academics and practitioners to rethink approaches issues on positive psychology. The style of the book would be academic but also designed in such a way for those non-academic oriented persons who are interested in the area to be able to benefit from the chapters. These include practitioners, policy makers and a broad-based readership. The book will also be designed for use by undergraduate students at least in the second year. The book will be designed to encourage engagement with the debates"--Provided by publisher.